Ground vibration effect evaluation due to blasting operations - Mohammad Forrukh Hossain Khan; Md. Jafar Hossain; Mohammad Tofayal Ahmed; Minhaj Uddin Monir; Md. Aliur Rahman; Tania Sultana Sweety; Faysal Ahamed Akash; Shaik Muntasir Shovon (Heliyon)
Addressing blast-induced ground vibration is crucial in the mining sector due to the potential for severe harm to surrounding inhabitants. This study aims to analyze ground vibration measurement data for ensuring safe blasting practices and proposes a modified scaled distance regression analysis model for predicting future underground vibrations at the Maddhapara Granite Mine in Bangladesh. The study meticulously captured structural underground vibration elements resulting from 46 stopes blasting events using the Micromate Instantel device. The United States Bureau of Mines (USBM) formula was applied to evaluate datasets correlating scaled distance with particle velocity. Through statistical analysis, the interrelation between peak particle velocity (PPV) and scaled distance (SD) at this location was elucidated, leading to the identification of a PPV equation for predicting values before blasting, thereby reducing underground vibration. The average predicted PPV value was found to be slightly higher than the actual PPV value, approximately 2.5 mm/s. Risk assessment for potential damage to various constructions was conducted in accordance with USBM and DIN 4150 standards. The study revealed that both PPV values and frequencies were below 6.636 mm/s and 9.5 Hz, respectively, falling within permissible limits for buildings. This finding significantly diminishes the risk of damage, establishing a safer environment for inhabitants and structures in proximity to the Maddhapara Granite Mine during blasting activities.